A 3’UTR-derived small RNA modulates the life cycle of the cholera toxin–encoding filamentous phage, CTXϕ - Anne Lippegaus; James R.J. Haycocks; Eoghan O’Driscoll; Marcel Sprenger; Kerstin Thriene; Elke-Martina Jung; Malte Siemers; Sebastian Krautwurst; David C. Grainger; Kai Papenfort (Proceedings of the National Academy of Sciences, 2026)
Bacteriophages (phages) are well known to be one of the major driving forces in bacterial evolution. This also applies to virulent microorganisms, such as the major human pathogen Vibrio cholerae , whose pathogenic potential and epidemic proliferation largely depends on the interaction with environmental phages. Specifically, integration of the CTXϕ phage genome into the first chromosome of V. cholerae also introduced the ctxAB genes, encoding the primary toxin responsible for the severe acute diarrheal disease, cholera. Whereas the mechanisms underlying CTXϕ-associated horizontal gene transfer and transcriptional control of the ctxAB genes have been intensively studied over the past years, posttranscriptional regulation affecting the CTXϕ life cycle has not been documented. Here, we report the identification and characterization of the CisR small RNA (sRNA) that is produced from the 3’UTR (untranslated region) of the prtV gene and inhibits the expression of the CTXϕ-encoded cep mRNA. CisR-mediated repression of cep involves Hfq-assisted base-pairing of the two transcripts and results in reduced CTXϕ production under stress conditions. We further demonstrate that transcription of prtV-cisR requires both the master quorum-sensing regulator HapR and CRP (cAMP receptor protein), a global regulator of carbon metabolism. Taken together, our work provides evidence that V. cholerae employs sRNA-mediated posttranscriptional gene regulation to coordinate CTXϕ activation with both cell density and nutrient availability.